Report of the Committee on the Elimination of Discrimination against Women, Eightieth Session - United Nations Department for General Assembly; Conference Management (United Nations, 2025)
This is the official report submitted to the General Assembly by the Committee on the Elimination of Discrimination against Women on its Eighty-eighth session (13–31 May 2024), Eighty-ninth session (7–25 October 2024), Ninetieth session (3–21 February 2025).